Future Earth : advancing civic understanding of the anthropocene - Dalbotten, Diana, 1959-; Hamilton, Patrick, 1958-; Roehrig, Gillian, 1968- (Hoboken, New Jersey : Wiley, 2014)
"Future Earth is a valuable practical guide for scientists from all disciplines including geoscientists, museum curators, science educators, and public policy makers"--
Machine generated contents note: Future Earth -- Advancing Civic Understanding of the Anthropocene Acknowledgements Preface Patrick Hamilton Chapter 1. Welcome to the Anthropocene Patrick Hamilton Chapter 2. The Anthropocene and the Framework for K-12 Science Education Fred N. Finley Chapter 3. Teacher Professional Development in the Anthropocene Devarati Bhattacharya, Gillian Roehrig, Anne Kern, and Mindy Howard Chapter 4. Climate Literacy and Scientific Reasoning Shiyu Liu, Keisha Varma, and Gillian Roehrig Chapter 5. Evaluation and Assessment of Civic Understanding of Planet Earth Julie C. Libarkin Chapter 6. Community-Driven Research in the Anthropocene Rajul Pandya Chapter 7. Geoscience Alliance: Building Capacity to Use Science for Sovereignty in Native Communities Nievita Bueno Watts, Wendy Smythe, Emily Geraghty Ward, Diana Dalbotten, Vanessa Green, Merv Tano, and Antony Berthelote Chapter 8. New Voices: The Role of Undergraduate Geoscience Research in Supporting Alternative Perspectives on the Anthropocene Diana Dalbotten, Rebecca Haaker-Santos, and Suzanne Zurn-Birkhimer Chapter 9. Shaping the Public Dialogue on Climate Change William Spitzer Chapter 10. Opportunities for Communicating Ocean Acidification to Visitors at Informal Science Education Institutions Douglas Meyer and Bill Mott Chapter 11. City-wide Collaborations for Urban Climate Education Steven Snyder, Rita Mukherjee Hoffstadt, Lauren B. Allen, Kevin Crowley, Daniel Bader, and Radley Horton Chapter 12. On Bridging the Journalism/Science Divide Bud Ward.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Geological time; Global environmental change; Communication in science; SCIENCE -- Earth Sciences -- General; Communication in science; Geological time; Global environmental change; Electronic books; Electronic books